Partisipasi Ibu dalam Pemasangan Live Trapp dengan Kepadatan Tikus di Kecamatan Trucuk Kabupaten Klaten - Tri Puji Pangesti; Wartini Wartini; Triyanta Triyanta (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2020)
Background: Rats are reservoirs of several diseases that leptospirosis, plague, tularamia, scrub typhes, rat bite fever / Ret Bites Fever (Santoso 2010). Leptospirosis is a disease caused by infection with Leptospira bacteria that attack animals and humans and can live in fresh water for about 1 month. The purpose of this study was to determine differences in the participation of Women in mice using live trapp arrest in the district of Klaten Regency Trucuk 2015.Method: This research is a quasi-experimental study (quasi experiment). This study uses a design approach posttest only control group and an analytic study. The sampling technique used in this research is purposive sampling with 100 respondents. Instruments using live trapp and Table Reports, Catching Mice, data were analyzed using univariate and bivariate (using the Mann-Whitney test with α = 0.05).Results: Results catches mice in the experimental group as much as 54 % and 32 % and a comparison group of mice density in the District of Klaten regency Trucuk 43 % . Bivariate analysis produces p-value = 0.002 .Conclusions: This study No different from the number of rats caught (p <0.05), with the participation of mothers in installing the live trap. Suggestion given to the District Government is seeking and coordinating Trucuk mother to jointly perform leptospirosis disease prevention through the installation of live trapp and motivate mother to escape from endemic regions leptospirosis.